Individually Planned Instruction in Light of Didactic Paradigms and Contemporary Instructional Systems - Jerković, Ljiljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
This paper discusses individually planned instruction in light of didactic paradigms, the possibility of varying instructional design and innovative instructional systems. Individually planned instruction is firmly grounded in the phenomenological and constructivist didactic paradigms. According to the phenomenological paradigm, the student is respected as an authentic being; this authenticity is supported by implementing individual upbringing and educational programs. The starting points of individually planned instruction as grounded in the phenomenological didactic paradigm are: recognition of discrete, specific activities (potential); transition from one zone of proximal development to the next; transition from structural indefiniteness to structural definiteness; a holistic approach to personality investigation; education aimed at one’s personality; efforts to allow one’s personality to be expressed as far as possible by moving up Maslow’s hierarchy of needs; and an individual’s “phenomenal world” or “phenomenal field”. Individually planned exercises based on the constructivist paradigm allow students to acquire subject matter in an active, self-accountable and self-organized way, i.e. discover, produce or “construct knowledge” about objective reality. The mainstays of individually planned instruction according to the constructivist didactic paradigm are: independent “knowledge construction”; contextual learning (internal and external contexts) and a holistic approach; learning how to learn; precisely defined expected learning outcomes and learning individualization; formative evaluation and self-evaluation, and the internal locus of control. This model of instruction partly has a foothold in the rationalist didactic paradigm, especially when it comes to working with underachievers and students with difficulties in learning and participation. Owing to its paradigmatic foundations, individually planned instruction is categorized as falling in developmental and personality-oriented instructional systems. Introducing elements of individually planned instruction to developmental instructional systems (problem-solving, discovery learning, heuristic, mentor-guided, other models of individualized instruction) can make them more humanistic and personality-oriented. Individually planned and inclusive education are developmental and personality-oriented instructional systems optimized, as inclusive individually planned instruction may be in the sense of future tendencies.